Fluorescence imaging host pathogen interactions: fifteen years benefit of hindsight…. (June 2018) - Aulner, Nathalie; Danckaert, Anne; Fernandes, Julien; Nicola, Marie-Anne; Roux, Pascal; Salles, Audrey; Tinevez, Jean-Yves; Shorte, Spencer L
Abstract : We consider in review current state-of-the-art fluorescence microscopy for investigating the host–pathogen interface. Our perspective is honed from years with literally thousands of microbiologists using the variety of imaging technologies available within our dedicated BSL2/BSL3 optical imaging research service facilities at the Institut Pasteur Paris founded from scratch in 2001. During fifteen years learning from the success and failures of introducing different fluorescence imaging technologies, methods, and technical development strategies we provide here a synopsis review of our experience to date and a synthesis of how we see the future in perspective for fluorescence imaging at the host–pathogen interface.